Trigonometry (11th Edition) Clone

Published by Pearson
ISBN 10: 978-0-13-421743-7
ISBN 13: 978-0-13421-743-7

Appendix A - Equations and Inequalities - Page 420: 40



Work Step by Step

$9x^{2}-12x+4=0$ $9x^{2}-6x-6x+4=0$ $3x(3x-2)-2(3x-2)=0$ $(3x-2)(3x-2)=0$ $(3x-2)=0$ or $(3x-2)=0$ $x=\frac{2}{3}$ or $x=\frac{2}{3}$ Check: Substituting $x=\frac{2}{3}$ in the equation, $9(\frac{2}{3})^{2}-12(\frac{2}{3})+4=0$ $\frac{36}{9}-\frac{24}{3}+4=0$ $4-8+4=0$ $0=0$ The value checks and the solution set is {$\frac{2}{3}$}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.